Hsa_circ_0054633 association of C peptide is related to IL‐17 and TNF‐α in patients with diabetes mellitus receiving insulin treatment. Issue 8 (17th July 2021) - Dai, Huixue; Hu, Fei; Yang, Xiangwei; Hu, Peng; Chu, Yudong; Bu, Shizhong
Abstract: Background: Chronic inflammation damaged the islet and resulted in dysfunction of T2D. Circular RNA is stable and better for biomarker in many diseases. Here, we aimed to identify potential circular RNA hsa_circ_0054633 that can be a biomarkers for the effects of insulin therapy in T2D. Methods: In this retrospective case‐control study, patients were from Li Huili Hospital, Ningbo, China, from February 10, 2019, to August 15, 2019. We included 47 healthy adults, 46 new‐onset T2D with insulin resistance, and 51 patients with insulin therapy. Serum inflammation factors were tested by ELISA assays. We selected hsa_circ_0054633 as a candidate biomarker and measured its concentration in serum by qRT‐PCR. The Pearson correlation test was used to evaluate the correlation between this circRNA and clinical variables. Results: Clinical data indicated that serum C peptide was increased in T2D treatment with insulin. Serum hsa_circ_0054633 was decreased in insulin treatment group. Hsa_circ_0054633 was negative correlated with C peptide ( r  = −0.2841, p  = 0.0433, ). IL‐1 and IL‐6, IL‐17, and TNF‐α were higher in T2D patients and decreased after insulin treatment, only IL‐17 and TNF‐α showed a positive correlation to hsa_circ_0054633 ( r  = 0.4825, p  < 0.0001, and r  = 0.6190, p  < 0.0001). The area under ROC curve was 0.7432, 0.5839, and 0.7573 for Hsa_circ_0054633, C peptide, and their combination. Conclusion: Hsa_circ_0054633 level was lower in T2D with insulin treatment than untreated and was a negative correlation with C peptide, and positively correlated with IL‐17 and TNF‐α, suggesting that hsa_circ_0054633 may be a potential early indicator of insulin treatment effect to improve inflammation condition. Abstract : Hsa_circRNA_0054633 was lower expression in T2D with insulin therapy. There was no significantly change between normal group and T2D without insulin therapy group ( p  > 0.05, T2D without insulin treatment vs. normal group). The level of Hsa_circRNA_0054633 in T2D patients with insulin treatment was marked lower in T2D treated with insulin than in without insulin ( p  < 0.05, vs. T2D without insulin treatment).